Interspecific variation in respiratory and photosynthetic parameters in Antarctic bryophytes - Davey, Martin C.; Rothery, Peter (New Phytologist, 1997)
Rates of carbon flux in 14 species of Antarctic bryophytes were measured under controlled conditions using an infra-red gas analysis system. The results were used to produce estimates of mode! parameters for respiration and photosynthesis. The relationships between respiration, photosynthesis, irradiance and temperature followed standard patterns. Temperature optima for gross and net photosynthesis were 10–20 and 0–20 °C respectively, suggesting that the plants were not truly psychrophilic. Photosynthesis was saturated at 30–270 μmol m−2s−1, consistent with the view that bryophytes are, physiologically, shade plants, although there was no evidence of photoinhibition over the range of irradiances tested (up to 700 μmol m−2s−1). Comparison of the results with environmental data suggests that photosynthesis is usually temperature-limited during daylight in the growing season. Therefore, any change in the temperature of the habitat could affect the productivity of the bryophytes. Rates of photosynthesis varied widely between species, and these relationships were largely maintained over the range of temperatures and irradiances tested. Photosynthetic rankings were correlated with the water availability in the plant habitats, supporting the hypothesis that water is the important factor in determining the distribution of populations in Antarctic habitats.